PENGARUH STRATEGI PEMECAHAN MASALAH DAN PEMAHAMAN BUDAYA TERHADAP PARTISIPASI MASYARAKAT DALAM PELESTARIAN KAWASAN LINDUNG TROWULAN, MOJOKERTO - Kresno Yulianto (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2010)
A lot of damage due to excessive exploitation has been done on the prominent archaeological site ofTrowulan, and this may partly be attributable to the minimum involvement of the community in the conservationefforts. The experimental study aims to assess the different effects of the two community- based conservationmethods—Participation Rural Appraisal (PRA) and Rapid Rural Appraisal (RRA)—on the communityparticipation in the preservation of the site. Four questions were raised as to (1) whether there is any differencebetween the participation of the community applying the PRA method and that of the community applying theRRA method; (2) whether there is any difference between the participation of the community with high levelcultural understanding applying the PRA method and that of the community with high level culturalunderstanding applying the RRA method; (3) whether there is any difference between the participation of thecommunity with low level cultural understanding applying the PRA method and that of the community with lowlevel cultural understanding applying the RRA method; and (4) whether there is any interaction between problemsolving strategy and cultural understanding in the participation of the community in the conservation of theTrowulan archaeological site. The 2x2 factorial design was applied on a sample consisting of 60 randomlyselected adult and married respondents from two villages in Kecamatan Trowulan. The study found (1) asignificant difference between the participation of the community applying the PRA method and that of thecommunity applying the RRA method; (2) no difference between the participation of the community with highlevel cultural understanding applying the PRA method and that of the community with high level culturalunderstanding applying the RRA method; (3) no difference between the participation of the community with lowlevel cultural understanding applying the PRA method and that of the community with low level culturalunderstanding applying the RRA method; and (4) interaction between problem solving strategy and culturalunderstanding in the participation of the community in the conservation of the Trowulan archaeological site.